Synthesis, Crystal Structure, Hirschfeld Surface Analysis and Catalytic Activity of a New Binuclear Zn(II) Complex Based on Homophthalic Acid and 2,2'-Bipyridine Ligands - Li-Hua Wang; Xi-Shi Tai (Bulletin of Chemical Reaction Engineering & Catalysis, 2022)
A new binuclear Zn(II) complex, [Zn2L2(BIPY)2(H2O)2](1) (H2L = homophthalic acid, BIPY = 2,2'-bipyridine) has been synthesized by one-pot method of homophthalic acid, 2,2'-bipyridine, zinc acetate dihydrate, and NaOH in water/ethanol (v:v = 1:1) solution. The structure of complex (1) was characterized by IR and X-ray single-crystal diffraction analysis. The results show that each Zn(II) ion is five-coordinated with two carboxylic O atoms from two homophthalate ligands (O2, O3 or O2a, O3a), two N atoms from two 2,2'-bipyridine ligands (N1, N2 or N1a, N2a) and one O atom from coordinated water molecule (O5 or O5a), and forms a distorted trigonal bipyramid coordination geometry. Complex (1) forms 1D chained structure and 3D network structure by the p-p interaction of 2,2'-bipyridine ligands. The Hirschfeld surface analysis of complex (1) was calculated. The catalytic performance of complex (1) has also been investigated for the oxidation of benzyl alcohol under O2 atmosphere. The optimal reaction temperature and pressure were 100 °C and 0.3 MPa for complex (1). Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).